Acumulação de Poluentes Inorgânicos por Macrófitas Aquáticas nos Reservatórios de Santana e Vigário, Barra do Piraí-RJ - Valitutto, Rosanna Strolla (2007)
Paraíba do Sul River (1,145 km long) crosses three of the most important and developed states of Brazil: Minas Gerais, São Paulo and Rio de Janeiro. It is the main water supply for more than 11 million people in Rio de Janeiro City, and it is also used extensively as a waste disposal system by industrial facilities in all three states. Moreover it receives untreated urban sewage from the cities it crosses. At the end of this very industrialised region, 40% of the river water is pumped up to form dams, named Santana and Vigário, for electrical generation. Then, the water runs down to form Guandú River, that will run to the second biggest Water Treat-ment Plant of the world. In those dams, aquatic macrophytes cover a large proportion of the sur-face area and has to be removed periodically. There has been an emphasis on converting this biomass into a useful resource, such as animal feed, fertilisers or for energy production. The aim of this work is to determine the extent of inorganic elements accumulation in the most abundant aquatic macrophytes (Salvinia auri-culata, Pistia stratiotes, Eichhornia crassipes e Eichhornia azurea) existing in those dams. For this purpose water samples were collected in three sites along the dams, filtered (0,45m), acidified and stored in refrigerator until analysis. Suspended solids were dried to constant weight at 60oC and stored. Plant samples from different species were collected, washed with water and packed in paper bags until lab. In the laboratory, plant samples were washed several times with distilled water, dried at 60oC during 2 hs, grounded and stored until analysis. The determination of the elements was performed using ICP-MS, ELAN 6000, Perkin-Elmer, Sciex. In general, all plant species accumulates the elements studied. However, each specie has a different bioaccumulation factor (BCF), which is the ratio between the element content in the plant and the element content in the water. Exception should be made for Ti, Cu, Zn, Rb, Sr, Se and Mo, whose BCF values were similar in all species